Los países ricos y los niños que trabajan: la paradoja occidental - Gianni Paone (Universidade do Porto, 2007)
In Europe child labour is not thoroughly studied or reported. The popular view is that child labour has been eradicated in Western societies. This is not the case, however, and it would be instructive to look more closely at the forms it takes in economically advanced countries. Understanding and identifying the similarities and differences between how the different regions approach the condition of childhood and adolescence will help lay the foundations for future strategies, policies and action plans to erase social inequalities. Child labour is also a big issue across a very wide range of sectors in industrialised countries. Child labour fills the interstices of a fragmented labour market, and is especially prevalent in various sectors of informal economy. In European countries, a large number of children work in seasonal, remunerated jobs, street trading and domestic work, for instance. The transition of some Eastern European countries to a market economy has also brought a resurgence of child labour in Central and Eastern Europe. Despite that, in some cases, children also in part work voluntarily for pocket money.